Hands-on Azure boards : configuring and customizing process workflows in Azure DevOps services - Chandrasekara, Chaminda; Herath, Pushpa (Apress, 2019)
Understand and explore the features and management of Azure Boards with this book, which also covers Azure Boards configuration and advanced administration. This book starts by setting up projects with Azure DevOps and gives an overview of Azure Boards and its features. You will then learn to set up team projects and how to effectively use Azure Boards to plan and execute work. Hands-on Azure Boards explains customizations, where you will understand the available options to track your work considering different scenarios. Next, you will learn visualizing with queries, charts, and dashboards along with reporting of Azure Boards. The author gives you hands-on lessons to set up Azure Boards and shows you how to handle multiple modules that are taken care of by different teams. You will also explore the security options in Azure Boards as well as a detailed demonstration of working with the REST API and CLI. Finally, you will work with useful extensions for Azure Boards and see how to use them more effectively and efficiently. After reading this book, you will be able to work with the Azure Boards capabilities available in Azure DevOps on-premise server and services to improve your software delivery process. You will: Plan and manage work with Azure Boards Use the REST API and command line interface with Azure Boards Extend Azure Boards with useful extensions to enhance its capabilities Customize Azure Boards to adapt it to your process Report and visualize work progress with Azure Boards.